Pengaruh Lingkungan Kerja dan Kepemimpinan Terhadap Semangat Kerja Pegawai Dinas Lingkungan Hidup (DLH) Kota Bima - Alfito; Muhammad Yusuf; Mawar Hidayati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the influence of the work environment and leadership on employee morale at the Bima City Environmental Service (DLH). The population in this study was 70 employees, consisting of 40 civil servants, 10 first aid workers, and 20 honorary employees. The sample size was 70, using a saturated sampling technique. The type of research conducted in this study was associative. The results showed that the work environment did not significantly influence employee morale at the Bima City Environmental Service (DLH); (b) leadership significantly influenced employee morale at the Bima City Environmental Service (DLH); and (c) the work environment and leadership did not significantly influence employee morale at the Bima City Environmental Service (DLH).